James Africanus Beale Horton on Naturalism, Baconianism, and Race Science in Victorian Philosophical Anthropology - Zeyad El Nabolsy (Journal of Modern Philosophy)
In this paper I show that James Africanus Beale Horton launched an internal critique of race science as it developed in the hands of Robert Knox, Carl Vogt, and James Hunt. The latter three held an inductivist Baconian conception of science. Horton shows that their practices as scientists and natural philosophers contradict their own conception of what one must do in order to do good science. Horton’s critique of race science has important implications for philosophical anthropology as it took shape over the course of the nineteenth century and for our understanding of the history of African philosophy in its global context.